PENTINGNYA UMKM MEMAHAMI FAKTOR INTERNAL DAN EKSTERNAL DALAM MENINGKATKAN KINERJA USAHANYA - Widodo, Adji; Harsono, Yhonanda; Saprudin, Udin (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
The purpose of this community service is to provide counseling to MSMEs who are partners of Waroeng Lengkong on Jl. SKKI, Serpong, South Tangerang. Participants in this community service consisted of Pamulang University lecturers, Pamulang University Management Study Program as resource persons, students, employees and owners of Waroeng Lengkong, and invited 8 MSME players who became partners at Waroeng Lengkong. The method used was to conduct presentations, counseling, discussions, and questions and answers to. Basically, the performance of the Micro, Small and Medium Enterprises (MSMEs) sector is influenced by two main factors, namely external factors and internal factors. Internal factors are factors that originate from within the business venture and can usually be controlled. Meanwhile, external factors are factors that come from outside business activities. At the community service event for Beginner MSMEs, it is important to immediately increase the ownership of their licenses so that they have legal force if their business is advanced, such as NIB, IUMK, Halal, PIRT, HAKI and BNPT. Improved network and additional marketing networks, according to their market segment, in order to increase sales turnover. Conduct orderly financial reports so that the development of business profits can be monitored and differentiated from personal funds. As for MSMEs that have developed, they should maintain the licenses they already have by maintaining product quality. Maintain the existing market, and explore further market opportunities. Conduct orderly financial reports so that the development of business profits can be monitored and differentiated from personal funds. Calculate if you really need additional capital. Do not do it if it is not in accordance with the designation because it will actually burden it as debt.